The Mediated Effect of Contextual Risk Factors on Trajectories of Violence: Results from a Nationally Representative, Longitudinal Sample of Hispanic Adolescents - Reingle, Jennifer M. (American journal of criminal justice, 2011)
The current study sought to estimate trajectories of violent behavior and evaluate the direct and indirect effects of contextual factors among Hispanics, stratified by gender. Relying on data from 3,719 Hispanic adolescents surveyed as a part of the National Longitudinal Study of Adolescent Health (Add Health), violence trajectories were estimated using group-based trajectory modeling. The results identified three groups of violence trajectories for both males and females (non-violent, desistors, and escalators) and there were considerable gender differences in the direct and indirect effects of risk and protective factors on violent behavior. Study limitations and policy implications are also discussed.